PENGARUH SOLVENCY MARGIN, BEBAN KLAIM, DAN RISK BASED CAPITAL TERHADAP RETURN ON EQUITY DENGAN KEPEMILIKAN MANAJERIAL SEBAGAI VARIABEL MODERASI. - Setiawan, Sukma Bayu (LPPM UNIVERSITAS INSAN PEMBANGUNAN INDONESIA, 2020)
ABSTRACT This research aims is to determine The Effect Of Solvency Margin, Claim Expanse Ratio, and Risk Based Capital to Return on Equity with Managerial Ownership As Moderating Variable. The research sample in this research is Sub Sector of Insurance Companies Listed On The Indonesia Stock Exchange period 2013-2017. The sampling method using purposive sampling method. There are 9 companies selected of 14 companies of sub sector companies listed in the Indonesia Stock Exchange as sample of this research. The analysis technique used moderated regression analysis (MRA) with EVIEWS 10 software. The result of this study indicated that (1) Solvency Margin has negatif effect on Return on Equity, (2) Claim Expenses Ratio has negative effect on Return on Equity, (3) Risk Based Capital has positive effect on Return on Equity, (4) Managerial ownership is not able to strengthen the positif effect of Solvency Margin on Return on Equity,but there is an interaction (5) Managerial Ownership is not able to weaken the negatif effect of Claim Expenses Ratio on Return on Equity, (6) Managerial Ownership is able to strengthen the positif effect of Risk Based Capital on Return on Equity.